Specialist physician perspectives on non-medical switching of prescription medications - Olivia S. Costa; Tabassum Salam; Amy Duhig; Aarti A. Patel; Ann Cameron; Jennifer Voelker; Brahim Bookhart; Craig I. Coleman (Journal of Market Access & Health Policy)
Introduction: A non-medical switch is a change to a patient’s medication regimen for reasons other than lack of clinical response, side-effects or poor adherence. Specialist physicians treat complex patients who may be vulnerable to non-medical switching. Objectives: To evaluate specialist physicians’ perceptions regarding the frequency of non-medical switch requests, and the impact on their patients’ outcomes and healthcare utilization. Methods: An online survey of randomly sampled physicians spending ≥10% of time providing patient care and having received ≥1 non-medical switch request during the prior 12-months. Results: Among 404 specialist physicians surveyed, non-medical switch requests were reported as very frequent or frequent by 35.0% of oncologists (for injectable cancer agents) and up to 80.3% of endocrinologists (for injectable anti-hyperglycemics). Respondents reported decreased medication effectiveness (25.0% of oncologists to 75.0% of dermatologists) and increased side-effects (32.5% of oncologists to 66.7% of psychiatrists). Most specialists reported very frequent or frequent increases in non-office visits (52.5% of oncologists to 75.3% of endocrinologists) and calls with pharmacies (57.5% of oncologists to 80.5% of rheumatologists) due to non-medical switching. Conclusions: Receipt of non-medical switching requests were common among specialist physicians. Non-medical switching may lead to negative effects on patient care and require increased healthcare utilization.